O ESPÍRITO SANTO NA SALA DE AULA: NARRATIVAS, SABERES E FAZERES DE PROFESSORES DE HISTÓRIA DA EDUCAÇÃO BÁSICA - Demuner, Angelo da Conceição (2021)
The main objective of the study is to analyze the teaching practice in the teaching of the History of Espírito Santo (HES) in the municipal schools of Vitória, in order to map and socialize these teaching practices that include and enable the development of studies on the theme. The raw material for the development of the research are the knowledge and explicit actions in the narratives of History teachers in the Vitória / ES city. Therefore, based on the theoretical and methodological assumptions of Oral History Bom Meihy (1996), Delgado (2006) and Alberti (2013), with an emphasis on Thematic Oral History, interviews were conducted that unveiled teachers' narratives about their training and the labor in the classroom. Hence the importance of studies and reflections that aim to subsidize the work of History teachers, considered as the main mediators in the production of historical knowledge. In the teachers' narratives, we identified the concern to work with the construction of the historical identity of the subjects belonging to Espírito Santo, seeking to valorize the Espírito Santo identity. We understand that HES can bring to the student the knowledge of the diverse cultural practices present in the local communities and in the region where they live. At the end, we developed a proposal with methodological alternatives for teaching HES in order to contribute to the teaching practices of History teachers.